Platelet‐activating factor: a potential therapeutic target to improve cancer immunotherapy - Qi Yan; Hemn Mohammadpour (Molecular Oncology)
The tumor microenvironment (TME) fosters cancer progression by supporting the differentiation and proliferation of myeloid‐derived suppressor cells (MDSCs), which play a critical role in suppressing immune responses and facilitating tumor growth. Recent findings by Dahal et al. reveal that platelet‐activating factor (PAF), a lipid mediator elevated in the TME, contributes to the differentiation of neutrophils into immunosuppressive neutrophils. They showed that inhibiting PAF signaling reduces MDSC‐mediated immunosuppression, thereby enhancing cytotoxic T‐cell activity. This approach may improve cancer immunotherapy outcomes, particularly when combined with checkpoint blockade therapies, suggesting a promising avenue for therapeutic development.